Nutritional profile of children bearing autism spectrum disorder - Caetano, Maria Vanuza (2018)
Objective: To evaluate the nutritional status and dietary intake of children bearing the autism spectrum disorder (ASD). Methods: The study had a quantitative, descriptive, exploratory and cross-sectional approach. Twenty-six children aged 3 to 10 years, with diagnosis of ASD, of both sexes, attended to in the city of Limoeiro do Norte, Ceará State, Brazil, participated in the study. Data was collected through interviews, guided by a socioeconomic questionnaire (age, family income, participants’ level of education, psychopharmacological treatment, age at diagnosis of ASD, ICD-10 coding, and clinical history); dietary history, application of three 24-hour recall, and anthropometric measurements (body weight, height, arm circumference and tricipital and subscapular skinfolds), with a subsequent calculation of the body mass index (BMI). Descriptive analysis was used and continuous variables were expressed as mean ± standard deviation and coefficient of variation. Results: Of the children evaluated, 10 (38.5%) were overweight (23.1%, n=6) or obese (15.38%, n=4) according to the BMI-for-age, and a further 10 children (38.5%) were at risk of overweight. The estimated energy requirement (EER) was above that recommended in 14 (53.85%) of the autistic patients. The intake of vitamins A (77%, n=20) and B6 (58%, n=15) and calcium intake (50%, n=13) were inadequate. Conclusion: Children with ASD evidence high overweight and obesity rates, and high inadequacy in vitamins and minerals intake.